Posttraumatic Stress Disorder and Domestic Violence - Nikulina, V.; Brumbaugh, C. C. (Encyclopedia of Domestic Violence, 2024)
'Posttraumatic Stress Disorder and Domestic Violence' published in 'Encyclopedia of Domestic Violence'